The Role of Information System Technology, Taxation Socialization on Taxpayer Compliance Moderated by Government Trust - Susanti, Heni; Ansori, Wakhid; Pardosi, Agnes Mariana; Pangaribuan, David; Triyana, Yeni; Nurhayati, Tutty (GoAcademica Research & Publishing, 2024)
The purpose of this study is to empirically test and analyze the impact of information system technology (e-filing), tax socialization, and government trust on the compliance of individual taxpayers at the North Bekasi Pratama Tax Office. Adopting an associative quantitative approach, the research employs a sample size of 100 respondents, selected using the Slovin formula. Data was collected using a questionnaire with a Likert scale. The findings of the study are presented below conclude that (1) The implementation of e-Filing has a discernible and substantial impact on taxpayer compliance, (2) The socialization of taxes has a positive and significant effect on the compliance of taxpayers, (3) The level of trust that the government is perceived to have by the public has a positive and significant impact on the extent to which taxpayers comply with the relevant regulations,(4) The degree of trust placed in the government by the public moderates the application of information system technology (e-filing) in influencing individual taxpayer compliance, (5) The degree of trust placed in the government by the public moderates the extent to which the government is able to socialize tax activities on the basis of individual taxpayer compliance. The findings of this study offer encouraging indications for the government, particularly the DJP, and taxpayers alike, in terms of maintaining the trust placed in them by the wider community. The efficacy of the system with respect to government services and researchers also contributes to the expansion of knowledge and awareness.